Mental Health Literacy, Stigma, and Help-Seeking Behavior Among Black Male College Students in Historically Black Universities - Bryan Gere; Nahal Salimi (American Journal of Men's Health)
Studies indicate that mental health literacy (MHL) is low among college students. Previous studies report that male college students score lower on MHL than female college students. MHL is connected to mental health help-seeking behavior. Black male college students are shown to be at higher risk for mental health problems such as depression, anxiety, and post-traumatic stress disorder, yet are less likely to seek help for these problems compared with other racial groups. Challenges with mental health can lead to significant negative consequences, such as poor academic performance, social isolation, and even suicide attempts. Stigma has been identified as an important factor that can influence the help-seeking behavior of male college students. Previous research has indicated that Black male college students in predominantly White institutions (PWIs) often struggle with seeking mental health compared with those in Historically Black Universities and Colleges (HBCUs). The purpose of the descriptive cross-sectional study was to investigate the relationships among MHL, stigma, and help-seeking behavior among Black males at HBCUs. The results indicate that having better mental health knowledge is linked to seeking help more often, stressing the need to enhance mental health understanding for better support-seeking. Seeking help was positively associated with reduced stigma. The implications for practitioners, policymakers, and administrators were explored, emphasizing the need for targeted, culturally sensitive interventions for young Black men in higher education. This study underscores the importance of addressing their specific challenges to enhance mental health and academic outcomes.